Vitamin C-rich guava consumed with mungbean dal reduces anemia and increases hemoglobin but not iron stores: A randomized controlled trial of food-to-food fortification in Indian children - Rani, Varsha; Moretti, Diego; Khetarpaul, Neelam; Thankachan, Prashanth; Zimmermann, Michael B.; Melse-Boonstra, Alida; Brouwer, Inge D. (Elsevier, 2024)
Background Adding vitamin C-rich fruit to staples containing iron could be an effective strategy to improve iron bioavailability and thereby reduce iron-deficiency anemia in children.